Mathematical modeling of metabolism via top-down and bottom-up approaches - Khatıbıpour, Mohammadjafar (Gebze Teknik Üniversitesi, Lisansüstü Eğitim Enstitüsü, 2020)
Biyolojik hücreler karmaşık dinamik sistemlerdir. Hücre içi moleküler etkileşimler, bu etkileşimlerin doğası ve işlevine bağlı olarak farklı etkileşim ağları şeklinde sınıflandırılabilirler. Gen regülasyon ağları, protein-protein etkileşim ağları ve metabolik ağlar, sistem biyolojisi ve sentetik biyoloji alanlarında sıklıkla ele alınan ve çalışılan ağlara örnek teşkil eder. Böylesi karmaşık sistemlerin hem teorik hem de deneysel alanda çalışılması gerekmektedir. Bu araştırmanın odağında, metabolik ağların analiz edilmesi ve hücresel metabolizmanın modellenmesinde, çalışılmasında ve incelenmesinde yardımcı olacak hesaplamalı araçların oluşturulması bulunmaktadır. Belirli bir koşulda aktif olan metabolik ağın belirlenmesi için kullanılabilecek hesaplamalı yöntemler iki ana grupta sınıflandırılabilir. Aşağıdan-yukarıya yöntemler, bir organizmanın metabolik modelini girdi olarak kullanarak ilgili koşulda aktif olan tepkimeleri optimizasyon yöntemiyle ve çözüm kümesini deneysel verilerle kısıtlayarak belirler. Yukarıdan-aşağıya yöntemler ise belli bir koşula ait metabolom verisini işleyerek o koşula ait aktif metabolik ağı belirlemeyi hedefler. Bu tez çalışması kapsamında, "JacLy" ismindeki yukarıdan-aşağıya yaklaşıma dayalı ve Jacobi temelli yöntem, kararlı-hal metabolom verisinin kovaryansından küçük ağların metabolik etkileşimleri tahmin etmek için geliştirildi. "Kinescope" isimli araç iseyarı-otomatik modelleme, simulasyon ve kinetik metabolik modellerin analizi için yeni bir hesaplamalı araç MATLAB'da geliştirildi. Bu tez çalışması kapsamında geliştirilen Jacly ve Kinescope araçlarının in silico deney verilerine uygulanarak validasyonu yapılarak uygulanabilirlikleri gösterildi.

Biological cells are complex dynamic systems. Intracellular molecular interactions can be categorized into different interaction networks based on the nature of interactions and their function. Gene regulatory networks, protein-protein interaction networks and metabolic networks are examples of frequently studied and addressed networks in the community of systems and synthetic biology. It is necessary to study such complex systems in both experimental and theoretical playgrounds. In this research, the focus is on the analytical study of the metabolic networks and the construction of computational tools that can help to model, study and analyze cellular metabolism. Computational methods for determination of the active metabolic networks at different cellular conditions/contexts are broadly categorized into two groups. Bottom-up approach in the context of metabolism is referred to those methods that use a metabolic model of the organism as an input to estimate the active reactions at the specified condition/context through optimization, while constraining the solution space based on the available experimental data. On the other hand, top-down approach is referred to those methods that aim to infer the active metabolic network at a specified condition/context by analyzing the corresponding metabolome data. In this work, "JacLy" is introduced as a top-down Jacobian-based method that is developed to infer metabolic interactions of small networks from the covariance of steady-state metabolome data. Kinetic models of intracellular biochemical reactions are very suitable tools to study and analyze cellular metabolism. However, it is not an easy task to make reliable kinetic models of metabolic networks and there are many challenging obstacles in the procedure. As an effort to ease kinetic modeling of biochemical reaction networks and also to provide a suitable platform to reconcile top-down and bottom-up approaches, "Kinescope" is introduced as a computational tool developed in MATLAB for semi-automatic construction, simulation and analysis of kinetic models of metabolism. Applicability of both computational tools developed in this work, JacLy and Kinescope, is verified through in silico experiments.
Yukarıdan aşağıya ve aşağıdan yukarıya yaklaşımlarla metabolizmanın matematiksel modellenmesi
Keywords: Biyomühendislik; Bioengineering